2018
DOI: 10.3389/fmicb.2018.02974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phototrophic Stream Biofilms Under Stress: Comparing Traditional and Novel Ecotoxicological Endpoints After Exposure to Diuron

Abstract: Stream biofilms have been shown to be among the most sensitive indicators of environmental stress in aquatic ecosystems and several endpoints have been developed to measure biofilm adverse effects caused by environmental stressors. Here, we compare the effects of long-term exposure of stream biofilms to diuron, a commonly used herbicide, on several traditional ecotoxicological endpoints (biomass growth, photosynthetic efficiency, chlorophyll-a content, and taxonomic composition), with the effects measured by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Likewise, groups with stronger fluorescence, which also constitutes the groups with large cells (compare Figures S2, S3 and S4), increased or remained stable, while those with lower fluorescence decreased or remained stable. In a previous experiment on periphyton exposed to 20 μg/L diuron by Sgier et al, a higher relative abundance of red-algae-like cells, identified as Bangia sp., was detected. In the same study, the proportion of decaying cells was higher.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Likewise, groups with stronger fluorescence, which also constitutes the groups with large cells (compare Figures S2, S3 and S4), increased or remained stable, while those with lower fluorescence decreased or remained stable. In a previous experiment on periphyton exposed to 20 μg/L diuron by Sgier et al, a higher relative abundance of red-algae-like cells, identified as Bangia sp., was detected. In the same study, the proportion of decaying cells was higher.…”
Section: Resultsmentioning
confidence: 88%
“…We hypothesized that diuron exerts a selection pressure on periphyton during its development leading to a shift in the community composition. These potential alterations in community composition, in turn, would change the nutritional quality of periphyton for the gastropod grazer and could be reflected in changes in its feeding activity and physiology, with similar effects being observed for fungicides affecting heterotrophic processes (cf. Zubrod et al).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the phenotypes among the species that changed in abundance were redundant with respect to phenotypic properties. There was also no MP-induced increase in the fraction of decaying cells as observed upon periphyton exposure to, for example, the herbicide Diuron (Sgier et al, 2018a). This suggests that MP do not seem to have a specific mode of action for microorganisms toxic to cells leading to cell death, which is the case for micropollutants (e.g., pesticides).…”
Section: Mp Changes Periphyton Microbial Community Structurementioning
confidence: 91%
“…In such ecosystems, biofilms occur at the boundary between the substrate and the water column. Stream biofilms are sensitive indicators of environmental stress [1] since their development, with regard to structure, taxonomic diversity and function, is extremely reliant on physical and chemical environmental factors [2].…”
Section: Introductionmentioning
confidence: 99%